Development of Learning Videos Using YouTube Integrated Video Prezi Applications on Fuel Injection Systems in Vocational Schools - Hendi Iswanto; Yayat Ruhiat; Cucu Atikah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The development of information and communication technology has touched various aspects of life, one of which is the world of education. Education cannot be separated from the development of IT. The Prezi video application can be used to create interesting learning video media for students. This research is a Research and Development (RD) research through a 4D development model, which consists of 4 stages, namely: (a) Define, (b) Design, (c) Develop, and (d) Disseminate. This study aims to develop material on the basic competence of gasoline injection systems for class XI Automotive Light Vehicle Engine Maintenance. Subject Automotive Light Vehicle Engineering ( TKRO) expertise program at a state vocational high school in Serang City. This research is limited to the development of media, which is validated by media experts, material experts, and student response trials. This is due to the limited research time. Data analysis techniques were obtained for product feasibility with a Likert scale. From the results of the stages carried out through this method, it can be concluded that the material expert validation was obtained by 87% with the very feasible category and the average media expert validation was obtained by 90% with the very feasible category to be used as an alternative learning video media to make it easier for students to understand material about Electronic Fuel Injection (EFI) Gasoline Injection system. Based on product trials conducted by 30 students, 87% of results were obtained in the very good category, or students were very interested in the learning videos that the researchers made.